Post Dural Puncture Headache following Spinal Anaesthesia for Caesarean Section - Karkada, EC (Nepal Journal of Obstetrics and Gynaecology, 2012)
NJOG 2011 Nov-Dec; 6 (2): 60-61 DOI: http://dx.doi.org/10.3126/njog.v6i2.6763